Core–Shell Spheroid‐Laden Microgels Crosslinked under Biocompatible Conditions for Probing Cancer‐Stromal Communication. Issue 12 (20th November 2022) - Zhu, Hongjia; Roode, Lianne W.Y.; Parry, Aled J.; Erkamp, Nadia A.; Rodriguez-Garcia, Marc; Narita, Masako; Shen, Yi; Ou, Yangteng; Toprakcioglu, Zenon; Narita, Masashi; Knowles, Tuomas P.J.
Abstract : Multicellular cancer spheroids (MCSs) have emerged as a promising in vitro model that recaptures many features of solid tumours in vivo. To generate cancer spheroids, cells are encapsulated in microgels with high throughput. While the biophysical properties of the cancer spheroid and biomaterial influence the function and behavior of the cells, characterization of these properties remains largely unexplored. In addition, many existing techniques lack control over cell positioning, resulting in the formation of spheroids with large variability. Herein, a versatile, microfluidic platform for generating biocompatible core–shell microgels with uniform cancer spheroids is reported. In addition, an in situ micromechanics measuring device to determine the stiffness of individual artificial cancer niches is used. The power of the microfluidics‐based method by making MCS‐laden microgels to model the interactions of stromal cancer cells is demonstrated. Together with in vivo data, it is shown that tumor cell proliferation is promoted by cocultured fibroblasts. Abstract : Cancer spheroids created using microfluidic technology provide a model system to study cancer cells and their interactions. The microgels surrounding the cells provide stiffness, creating spherical cancer niches, while letting nutrients and waste through. Comparing in vivo experiments on stromal‐cancer cell interactions with the model shows that the uniform cancer spheroids capture the in vivo behavior.